Studi Geografi Penduduk Tentang Dampak Pernikahan Dini terhadap Remaja di Indonesia - Marlina Marlina; Sukri Nyompa (LaGeografia, 2026)
Early marriage is a demographic issue. It remains a significant social problem in Indonesia, negatively impacting the health of adolescents, particularly girls. This study examines the impact of early marriage on the physical and reproductive health of adolescents, along with its impact on the health of their offspring. The research method employed involved a literature review of various research findings, official agency reports, and contemporary scientific publications related to the subject matter. The findings indicate that adolescent marriage increases the risk of pregnancy problems, including anemia, hypertension, hemorrhage, and maternal and neonatal mortality. This condition is exacerbated by a lack of physical readiness, inadequate reproductive health information, and socioeconomic conditions that encourage early marriage. Furthermore, the offspring of adolescent mothers face an increased risk of low birth weight and stunting caused by inadequate nutrition. The study's conclusions emphasize the importance of collaboration between families, communities, and the government in improving health education and child marriage prevention programs to improve the well-being and health status of adolescents in Indonesia.